Pengembangan LKPD Berbasis Augmented Reality Dalam Metode Praktikum Materi Organ Indera Untuk Meningkatkan Penguasaan Konsep Siswa Dan Keterampilan Proses Sains - Indriani, Dini; Hindriana, Anna Fitri; Sulistyono, Sulistyono (Program Studi Pendidikan Biologi, Sekolah Pascasarjana Universitas Kuningan, 2022)
This study aims to develop Student Worksheets Based on Augmented Reality that are used in practicum material on sensory organs. Currently, there are still schools that do not have a torso, so this Student Worksheet can be used as an alternative for use in practicum on sensory organs. The research was carried out at MAN 3 Cirebon from April to September 2022 in class XI MIA 5 as the control class and class XI MIA 4 as the experimental class. The research was carried out using the Research and Development (R & D) method and the analysis, design, development, implementation, and evaluation (ADDIE) development model. The research sampling technique is random sampling. The data collection instruments used were expert assessment sheets, tests, student science process skills rubrics and student questionnaires. The results showed that the average validation results from the two validators was 93.4% and the student worksheet implementation was 96.3%. Concept mastery has increased as evidenced by the N Gain results of the control class using ordinary Student Worksheets with torsos of 12.2% while the N Gain results of the experimental class using Augmented Reality Based Student Worksheets are valued at 56.6%. There is also a difference in the average value of science process skills, namely the control class is 74.73 while the science process skills in the experimental class are 92.62. This shows that the developed Augmented Reality-Based Student Worksheets can improve students' mastery of science concepts and process skills. Student responses to Student Worksheets Based on Augmented Reality can also be categorized as good.